2018
DOI: 10.1002/gcc.22685
|View full text |Cite
|
Sign up to set email alerts
|

Clonal evolution through genetic bottlenecks and telomere attrition: Potential threats to in vitro data reproducibility

Abstract: Tissue cultures of immortalized human cells, also known as established cell lines, are broadly accessible and cost‐efficient tools for biomedical research. We here review potential genetic sources of systematic error in cell line experiments due to clonal evolution in vitro. In particular, the authors highlight alterations in telomere function over prolonged culture and population bottlenecks, respectively, as two commonly overlooked phenomena that can result in significant alterations in cell line genotypes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Continuous cell passaging might cause clonal selection and consequent loss of heterogeneity following disruption of the original tumor structure and microenvironment. Gisselsson et al [105] comprehensively reported about the possible causes of clonal selection, specifically identifying (i) alterations in telomere function occurring over prolonged in vitro culture, and (ii) population (or genetic) bottlenecks (i.e., a significant decrease in the size of a biologically reproductive population that could be caused by factor(s) limiting the number of cells allowed to proliferate) as frequently neglected phenomena that may cause alterations in (cancer) cell line genotypes even after few passages in vitro. Compared to patient tumors, BC cell lines show a higher mutation frequency, which, over many in vitro passages, may originate a cell different from the original one.…”
Section: Breast Cancermentioning
confidence: 99%
“…Continuous cell passaging might cause clonal selection and consequent loss of heterogeneity following disruption of the original tumor structure and microenvironment. Gisselsson et al [105] comprehensively reported about the possible causes of clonal selection, specifically identifying (i) alterations in telomere function occurring over prolonged in vitro culture, and (ii) population (or genetic) bottlenecks (i.e., a significant decrease in the size of a biologically reproductive population that could be caused by factor(s) limiting the number of cells allowed to proliferate) as frequently neglected phenomena that may cause alterations in (cancer) cell line genotypes even after few passages in vitro. Compared to patient tumors, BC cell lines show a higher mutation frequency, which, over many in vitro passages, may originate a cell different from the original one.…”
Section: Breast Cancermentioning
confidence: 99%
“…Such monotypic cell models have led to important discoveries but have notable limitations. Immortalized cell lines can undergo significant genotypic alterations within a few passages in vitro which are potential threats to data reproducibility [4][5][6]. Furthermore, transformed cell lines often have altered pathway expression compared to primary cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…3. The telomeric dynamics during this same time‐period in culture is illustrated in Reference , fig. 5.…”
mentioning
confidence: 98%
“…Diploid immortalized cells in culture show dynamic nuclear organizational changes. Gisselsson et al, examined the clonal evolution of Bj‐5ta cells starting from an identical passage and studied independently in three laboratories. In vitro evolution occurred over a few passages and was evident by nuclear remodeling and genetic diversity.…”
mentioning
confidence: 99%
See 1 more Smart Citation